2021
DOI: 10.1155/2021/9918060
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Provision of Trade Credit in a Dual-Channel Supply Chain

Abstract: This study focuses on a a dual-channel supply chain that consists of a capital-constrained brick-and-mortar retailer and a manufacturer, where a manufacturer can simultaneously sell products through a traditional retail channel and a direct online channel. Supplementary pricing strategy and competitive pricing strategy are simulated in our model, and we find that the former one is the better choice for the manufacturer when the retailer suffers capital constraints. In our analysis, the capital constraint on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Using a switching regression method and incorporating the simultaneous decisions taken by the financial banks to provide credit and decision of the firms to implement same they arrived at helpful managerial decisions. Wan et al [10] considered a dual channel in which a manufacturer can sell his products through retail supply channel and at the same time directly to consumers through an online product supply channel. They developed a model on competitive and supplementary product pricing strategies, and observed that instead of unconditional provision of trade credit, the manufacturer's provision of trade credit should be strategic.…”
Section: Original Research Articlementioning
confidence: 99%
“…Using a switching regression method and incorporating the simultaneous decisions taken by the financial banks to provide credit and decision of the firms to implement same they arrived at helpful managerial decisions. Wan et al [10] considered a dual channel in which a manufacturer can sell his products through retail supply channel and at the same time directly to consumers through an online product supply channel. They developed a model on competitive and supplementary product pricing strategies, and observed that instead of unconditional provision of trade credit, the manufacturer's provision of trade credit should be strategic.…”
Section: Original Research Articlementioning
confidence: 99%
“…Considering optimal length of a cycle, preservation technology, product price and trade credit financing, Mashud et al [11] studied how trade credit and product preservation technology can influence the rate of deterioration of a product and flexible retail financing. In a study of a manufacturer-retailer conventional channel and a manufacturer-consumer online channel, a dual-channel system, Wan et al [12] formulated a model on pricing strategies, and inferred that credit should be strategically provided instead of unconditional provision. Mahata and Mahata [13] considered a dynamic situation involving the sale of deteriorating items with varying demand rate with respect to inventory level and length of credit period.…”
Section: Introductionmentioning
confidence: 99%